2018
DOI: 10.1021/acs.jnatprod.7b00945
|View full text |Cite
|
Sign up to set email alerts
|

Natural Deep Eutectic Solvents: Properties, Applications, and Perspectives

Abstract: As functional liquid media, natural deep eutectic solvent (NADES) species can dissolve natural or synthetic chemicals of low water solubility. Moreover, the special properties of NADES, such as biodegradability and biocompatibility, suggest that they are alternative candidates for concepts and applications involving some organic solvents and ionic liquids. Owing to the growing comprehension of the eutectic mechanisms and the advancing interest in the natural eutectic phenomenon, many NADES applications have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
448
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 881 publications
(515 citation statements)
references
References 79 publications
3
448
0
8
Order By: Relevance
“…The predicted C DES levels implied the use of a significantly higher water amount compared with previous results from polyphenol extraction with DES, which indicated that 80% (w/w) to be the most appropriate C DES for high extraction yield [23][24][25][26]. Suitable DES mixing with water is indispensable for regulation of properties crucial to solid-liquid extraction, such as viscosity and polarity [27]. However, C DES cannot be below a certain level because excessive water amount would cause DES decomposition and therefore the intrinsic DES properties would be abolished [28].…”
Section: Optimisation Of Extraction Performancementioning
confidence: 69%
“…The predicted C DES levels implied the use of a significantly higher water amount compared with previous results from polyphenol extraction with DES, which indicated that 80% (w/w) to be the most appropriate C DES for high extraction yield [23][24][25][26]. Suitable DES mixing with water is indispensable for regulation of properties crucial to solid-liquid extraction, such as viscosity and polarity [27]. However, C DES cannot be below a certain level because excessive water amount would cause DES decomposition and therefore the intrinsic DES properties would be abolished [28].…”
Section: Optimisation Of Extraction Performancementioning
confidence: 69%
“…The term Deep Eutectic Solvent (DES) [1][2][3] is most commonly used to describe low melting liquids formed by combining organic salts such as choline chloride with urea or other hydrogen-bond donor components including carboxylic acids and alcohols. DES were initially popularised 4 as lower cost and more environmentally benign (greener) variants of non-volatile ionic liquids and have been used as non-aqueous electrolyte solutions, 5 and media for nanoparticle and materials synthesis, [6][7][8][9] solvents for catalysis 10 and as vehicles for delivery of active pharmaceutical ingredients 11,12 have been extensively investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…DESs are af ascinating example in which hydrogen-bondmediated anion binding,ak ey theme in supramolecular chemistry, [4] leads to significant changes in the properties of the bulk material. Like traditional ionic liquids,m any DESs have low vapour pressure,low flammability,and awide liquid range,b ut they also have additional advantages,i ncluding ease of preparation and the use of relatively inexpensive, nontoxic components.T hese solvents are being extensively explored for aw ide range of uses,i ncluding metal processing, [5] organic synthesis/catalysis, [6] nanomaterials synthesis, [7] analytical chemistry, [8] biotechnology, [9] and energy applications. [10] There has previously been considerable interest in structuring traditional ILs into soft materials,s uch as gels,t o generate "ionogels".…”
mentioning
confidence: 99%